Hierarchical porous molybdenum-bismuth composite metal oxide catalyst and preparation method and application thereof
By preparing the multi-stage porous molybdenum bismuth composite metal oxide catalyst Mo12Bi1.5Fe1.5Co5CexGdyK0.5O/TiO2, the problem of low selectivity of existing catalyst products is solved, and the reaction efficiency and catalytic activity of methacrylate is improved by selective oxidation of isobutene to prepare methacrylate .
Patent Information
- Application Number
- CN202310859210.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-13
AI Technical Summary
The existing Mo-Bi composite metal oxide catalysts have low product selectivity during isobutene selection oxidation to prepare methacrylate, and the specific surface area of the simple Mo-Bi catalyst is small, which is not conducive to elemental dispersion and leads to an increase in reaction by-products. The target product selectivity decreases.
Using the multi-stage porous molybdenum-bismuth composite metal oxide catalyst Mo12Bi1.5Fe1.5Co5CexGdyK0.5O/TiO2, the precipitation of multi-stage porous TiO2 support and composite metal oxide is improved, and the dispersion of active components and the synergistic effect between rare earth metals is improved. , enhance the product selectivity of the catalyst.
The product selectivity of the catalyst and the number of reactive oxygen species are improved, the catalytic activity is enhanced, the formation of hot spots in the reaction bed is reduced, and the reaction efficiency of methacreal is improved by selective oxidation of isobutene.
Smart Images

Figure CN119303588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst preparation, and in particular to a multi-level porous molybdenum-bismuth composite metal oxide catalyst and a preparation method and application thereof. Background Art
[0002] As a kind of low-carbon olefin, isobutylene is mainly derived from petroleum cracking and isobutane dehydrogenation technology. With the increase in domestic isobutylene production, the high-value clean utilization of isobutylene has become increasingly important. The downstream products of isobutylene mainly include methyl methacrylate, isoprene, butyl rubber and polyisobutylene. Judging from the consumption structure of isobutylene in recent years, the consumption structure of isobutylene using isobutylene as raw material to prepare methyl methacrylate accounts for a large proportion. Methyl methacrylate is an extremely important raw material and polymerization monomer in chemical production, and is widely used in automobiles, construction, electronics, advertising and decoration, etc.
[0003] There are three main process routes for preparing methyl methacrylate by oxidation of isobutylene: oxidation of isobutylene to methacrolein (MAL), then oxidation to methacrylic acid, and finally esterification to methyl methacrylate; this method has the disadvantages of long process and low yield. Isobutylene is oxidized to methacrylic acid in one step, and then esterified to methyl methacrylate. This method has not yet been industrialized. Isobutylene is oxidized to MAL, and then directly oxidized and esterified with methanol to methyl methacrylate; due to the shorter synthesis route, this method can greatly reduce production costs and is relatively green. From a scientific point of view, the selective oxidation of isobutylene to prepare MAL is one of the necessary steps in the isobutylene oxidation method and also the most critical step. On the one hand, isobutylene containing two active α-CH3 in the same position and the more active product MAL are prone to deep oxidation under the reaction conditions; on the other hand, the reaction by-products and unreacted isobutylene are not conducive to the catalyst used in the subsequent oxidation step. Therefore, how to achieve efficient selective activation of the CH bond of isobutylene and convert it into MAL is a very challenging technical problem and has great theoretical research significance.
[0004] Since the selective oxidation of isobutylene to prepare MAL is an exothermic reaction, in the process of obtaining the target product, the by-products will also increase, resulting in a decrease in the selectivity of the target product. The reaction is usually activated by catalysis of Mo-Bi composite metal oxides. The preparation methods of Mo-Bi composite metal oxides include direct mixing, coprecipitation, and hydrothermal synthesis. The direct mixing method is to mix the metal precursor solution of Mo with the metal precursor solution containing Bi, Fe, Co, etc., without using a precipitant for precipitation. The coprecipitation method mixes the metal precursor solution of Mo with the metal precursor solution containing Bi, Fe, Co, etc., and then adjusts the pH value of the slurry. Patents CN103721722A and CN103157483A involve Mo-Bi composite metal oxide catalysts prepared by coprecipitation. The catalyst prepared by this method is affected by many aspects, such as the addition and precipitation order of metal ions, the adjustment of pH value, the calcination temperature, etc. The hydrothermal synthesis method is generally used for laboratory preparation. The prepared catalyst contains more complex phases, there is a synergistic effect between phases, and the catalyst selectivity is good. The pure Mo-Bi catalyst has a small specific surface area, which is not conducive to the dispersion of each element, and the product selectivity is low. Therefore, further research on Mo-Bi composite metal oxides is needed in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide a large specific surface area multi-level porous molybdenum bismuth composite metal oxide catalyst and its preparation method and application, so as to overcome the defect of poor product selectivity of the molybdenum bismuth composite metal oxide catalyst in the prior art.
[0006] In order to achieve the above object, the present invention provides a multi-level porous molybdenum-bismuth composite metal oxide catalyst, the multi-level porous molybdenum-bismuth composite metal oxide catalyst has a general formula of Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O / TiO2, wherein 0<x≤1.2, 0<y≤0.3. The catalyst comprises a carrier and a composite metal oxide, wherein the composite metal oxide is dispersed in the carrier, wherein the carrier is multi-level porous TiO2, and the composite metal oxide is a composite oxide of molybdenum, bismuth, iron, cobalt, potassium and at least two rare earth metals, and the general formula is: Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O.
[0007] In the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention, the weight percentage of the carrier to the catalyst is 30% to 80%.
[0008] In order to achieve the above object, the present invention also provides a method for preparing a multi-level porous molybdenum-bismuth composite metal oxide catalyst, comprising the following steps:
[0009] Step 1, preparing a multi-level porous TiO2 carrier;
[0010] Step 2, preparing a solution containing a Mo precursor, a Bi precursor, a Fe precursor, a Co precursor, a Ce precursor, a Gd precursor, and a K precursor;
[0011] Step 3, mixing the multi-level porous TiO2 carrier with the solution described in step 2, adding a precipitant for deposition and precipitation, and obtaining a multi-level porous molybdenum-bismuth composite metal oxide catalyst.
[0012] The preparation method of the multi-level porous molybdenum-bismuth composite metal oxide catalyst described in the present invention, wherein the preparation method of the multi-level porous TiO2 carrier comprises the following steps: mixing the mesoporous template and the macroporous template evenly, adding a titanium precursor, aging, drying, and calcining to obtain the multi-level porous TiO2 carrier.
[0013] The preparation method of the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention, wherein the mesoporous template agent is F127 and / or P123; the macroporous template agent is PS ball and / or PMMA ball.
[0014] The preparation method of the multi-level porous molybdenum-bismuth composite metal oxide catalyst described in the present invention, wherein the Mo precursor is ammonium molybdate and / or molybdenum trioxide, and the Bi precursor, Fe precursor, Co precursor, Ce precursor, Gd precursor, and K precursor are nitrates or chlorides of Bi, Fe, Co, Ce, Gd, and K.
[0015] The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention, wherein the precipitant is at least one of ammonia water, urea, and sodium hydroxide, and the amount of the precipitant added is such that the pH value of the mixed solution is 5.0-7.0.
[0016] The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention, wherein the method for preparing the multi-level porous TiO2 carrier comprises the following steps:
[0017] The mesoporous template is dissolved in ethanol, hydrochloric acid and / or acetic acid are added, and stirred; the macroporous template is added, stirred, and then the titanium precursor is added, aged, dried, and calcined to obtain a multi-level porous TiO2 carrier.
[0018] The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention, wherein the drying method is rotary evaporation and / or oven drying.
[0019] In order to achieve the above object, the present invention further provides the use of the above multi-level porous molybdenum-bismuth composite metal oxide catalyst in the selective oxidation of isobutylene to prepare methacrolein.
[0020] Beneficial effects of the present invention:
[0021] The multi-level porous molybdenum-bismuth composite metal oxide catalyst prepared by the present invention has a large specific surface area and contains at least two rare earth metals at the same time, which promotes high dispersion of active components and synergistic effects between rare earth metals, increases the number of active oxygen species, and thus improves the product selectivity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a field emission scanning electron microscope image (FESEM) (100 nm) of the mesoporous-macroporous TiO2 in Example 1 of the present invention.
[0023] Figure 2 This is a field emission scanning electron microscope image (FESEM) (1 μm) of the mesoporous-macroporous TiO2 in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is described in detail below. The following implementation modes are implemented on the premise of the technical scheme of the present invention, and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following implementation modes. The structures or experimental methods of specific conditions are not specified in the following implementation modes, and generally conventional conditions are followed.
[0025] The present invention provides a multi-level porous molybdenum-bismuth composite metal oxide catalyst, wherein the multi-level porous molybdenum-bismuth composite metal oxide catalyst has a general formula of Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O / TiO2, wherein 0<x≤1.2, 0<y≤0.3. The catalyst comprises a carrier and a composite metal oxide, wherein the composite metal oxide is dispersed in the carrier, the carrier is multi-level porous TiO2, and the composite metal oxide is a composite oxide of molybdenum, bismuth, iron, cobalt, potassium and at least two rare earth metals.
[0026] The molybdenum-bismuth composite metal oxide catalyst of the present invention has a multi-level pore structure and contains at least two rare earth metals. Due to the large specific surface area, the active components are highly dispersed, and there is a synergistic effect between the rare earth metals, which increases the number of active oxygen species and thus improves the product selectivity of the catalyst.
[0027] In one embodiment, the weight percentage of the carrier of the present invention to the catalyst is 30% to 80%, preferably 50 to 70%.
[0028] The carrier of the present invention is TiO2, and the catalyst of the present invention can be expressed as: Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O / TiO2, wherein 0<x≤1.2, preferably x=0.2-0.8, 0<y≤0.3, preferably y=0.1-0.2. In one embodiment, TiO2 is multi-level porous TiO2.
[0029] In one embodiment, the preparation method of the multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention comprises the following steps:
[0030] Step 1, preparing a multi-level porous TiO2 carrier;
[0031] Step 2, preparing a solution containing a Mo precursor, a Bi precursor, a Fe precursor, a Co precursor, a Ce precursor, a Gd precursor, and a K precursor;
[0032] Step 3, mixing the multi-level porous TiO2 carrier with the solution described in step 2, adding a precipitant for deposition and precipitation, and obtaining a multi-level porous molybdenum-bismuth composite metal oxide catalyst.
[0033] In one embodiment, the preparation method of multi-level porous TiO2 of the present invention includes the following steps: dissolving a mesoporous template in ethanol, adding hydrochloric acid and / or acetic acid, and stirring; adding a macroporous template, stirring, and then adding a titanium precursor, aging, drying, and calcining to obtain a multi-level porous TiO2 carrier.
[0034] In one embodiment, the mesoporous template is F127 (acrylated polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer) or P123; the macroporous template is PS sphere or PMMA sphere.
[0035] In one embodiment, the titanium precursor is titanium isopropoxide, titanium tetrachloride, or tetrabutyl titanate.
[0036] In the preparation process of the hierarchical porous TiO2 of the present invention, the addition of hydrochloric acid and acetic acid can prevent the titanium precursor such as titanium isopropoxide from being over-hydrolyzed. In one embodiment, in the preparation process of the hierarchical porous TiO2 carrier, the aging temperature is 30-50°C, the aging time is 1-6 days, the drying temperature is 100-140°C, the drying time is 6-18 hours, the calcination temperature is 350-600°C, and the calcination time is 1-10h.
[0037] In one specific embodiment, the preparation method of the multi-level porous TiO2 carrier of the present invention is:
[0038] The multi-level porous TiO2 was prepared by the soft template method. The mesoporous template was dissolved in ethanol, and hydrochloric acid and acetic acid were added and stirred for 10 minutes. The macroporous template was added and stirred at room temperature for 6 hours. After adding titanium isopropoxide, the stirring was continued at room temperature for 3 hours. The mesoporous-macroporous TiO2 carrier was obtained by aging at a certain temperature for 5 days, drying at 120°C for 12 hours, and then calcining in air at a certain temperature for 4 hours.
[0039] In one embodiment, the Mo precursor is ammonium molybdate or molybdenum trioxide, and the Bi precursor, Fe precursor, Co precursor, Ce precursor, Gd precursor, and K precursor are nitrates or chlorides of Bi, Fe, Co, Ce, Gd, and K. In another embodiment, step 1 of the present invention is: dissolving the Mo precursor in water to obtain solution A; dissolving the Bi precursor, Fe precursor, Co precursor, Ce precursor, Gd precursor, and K precursor in a dilute nitric acid solution to obtain solution B; adding solution B to solution A and stirring to obtain a composite metal oxide precursor slurry.
[0040] Step 3 is: mixing the multi-level porous TiO2 carrier with the solution described in step 2, adding a precipitant for deposition and precipitation, and obtaining a multi-level porous molybdenum-bismuth composite metal oxide catalyst.
[0041] Among them, the TiO2 carrier is, for example, the multi-level porous TiO2 carrier prepared as described above, the multi-level porous TiO2 carrier is added to the solution obtained in step 2, and then a precipitant is added to adjust the pH value of the solution. In one embodiment, the pH value is, for example, 5.0-7.0, preferably 6.5, and then aged, dried, calcined, and pressed into tablets to obtain a multi-level porous molybdenum-bismuth composite metal oxide catalyst.
[0042] The present invention does not specifically limit the precipitant, for example, ammonia water, urea and sodium hydroxide, etc. In one embodiment, during the preparation of the multi-level porous molybdenum-bismuth composite metal oxide catalyst, the aging temperature is 30-50°C, the aging time is 10-60min, the drying method is rotary evaporation or / and oven drying, the drying temperature is 100-140°C, the drying time is 6-24 hours, the roasting temperature is 400-500°C, preferably 450°C, and the roasting time is 1-10h.
[0043] The macroporous template PS ball and PMMA ball used in the present invention have a regular spherical morphology, and the synthesized multi-level porous titanium dioxide has a high specific surface area of 200m 2 ·g -1 The large pore size is conducive to the uniform dispersion and mass transfer of active components.
[0044] The multi-level porous molybdenum-bismuth composite metal oxide catalyst of the present invention is suitable for the selective oxidation of isobutylene to prepare methacrolein, and can improve the selectivity of the target product methacrolein.
[0045] The present invention adopts a multi-level porous Mo-Bi composite metal oxide, which can utilize the large specific surface area and multi-level pore structure of the material. On the one hand, the active species are better dispersed, which is beneficial to the rapid diffusion of reactants and products, and the synergistic effect between rare earth metals is more conducive to the regulation of active oxygen species, thereby improving catalytic activity and selectivity; on the other hand, the multi-level pore structure is easy to diffuse heat and avoid the formation of hot spots in the reaction bed, and the reaction process can be effectively controlled.
[0046] The technical solution of the present invention will be described below through specific embodiments.
[0047] Source of raw materials or equipment:
[0048] F127 (Sigma), ethanol (Chengdu Kelong Chemical Co., Ltd.), hydrochloric acid (Chengdu Kelong Chemical Co., Ltd.), acetic acid (Chengdu Kelong Chemical Co., Ltd.), titanium isopropoxide (Annage Chemical), nitric acid (Chengdu Kelong Chemical Co., Ltd.), ammonium molybdate (Chengdu Kelong Chemical Co., Ltd.), bismuth nitrate (Tianjin Chemical Reagent Factory No. 3), ferric nitrate (Xilong Chemical Co., Ltd.), cobalt nitrate (Xilong Scientific Co., Ltd.), potassium nitrate (Sichuan Xilong Chemical Co., Ltd.), cerium nitrate (Chengdu Kelong Chemical Co., Ltd.), gadolinium nitrate (Aladdin Reagent), fixed bed microreaction evaluation device (Tianjin Pengxiang Technology Co., Ltd.), gas chromatograph (Shimadzu GC-2014C).
[0049] Evaluation and analysis methods:
[0050] The reaction conditions for selective oxidation of isobutylene are 360-420°C, atmospheric pressure, and the volume space velocity of the feed gas relative to the catalyst is 9200 h -1 , the space velocity ratio of air to isobutylene is 96:4.
[0051] In the reaction of the present invention, the definitions of conversion, selectivity and yield are as follows:
[0052] Isobutylene conversion rate (%) = 100 × total carbon number of the generated product / carbon number of the supplied isobutylene
[0053] MAL selectivity (%) = 100 × carbon number of methacrolein produced / carbon number of isobutylene supplied
[0054] MAL yield (%) = conversion rate (%) × selectivity (%) / 100
[0055] In one embodiment of the present invention, the reaction product is analyzed online with methane as the associated gas by gas chromatograph (Shimadzu GC-2014C), and methane, ethane, ethylene, isobutylene and other gases are detected by Al2O3 column, CO x The products were detected by TDX-01 column, and other products such as acetic acid, acetone, and methacrolein were detected by DB-5 column. The relative correction factors of various organic products were calculated. The conversion rate and selectivity were calculated based on carbon balance.
[0056] Example 1
[0057] Dissolve 6g F127 in 75mL ethanol, stir at room temperature for 30min, add 6g hydrochloric acid and stir for 5min, add 6g acetic acid and stir for 5min, continue to stir at 40℃ for 2h. Add 15g PS balls and stir at room temperature for 6h, add 8.5g titanium isopropoxide and stir at room temperature for 3h. Aging at 30℃ for 5 days. Calcinate at 450℃ in air for 4h to obtain meso-macroporous TiO2. Through N2 adsorption and desorption experiments, it is known that the specific surface area of TiO2 is 268m 2 ·g -1 The average pore size of the macropores is 303nm, and the average pore size of the mesopores is 16nm.
[0058] In a round-bottom flask, 10.59 g (NH4)6MoO 24 ·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 0.43g Ce(NO3)3·6H2O, 0.45g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred for 30min at room temperature to obtain solution B. At 50℃, solution B was added dropwise to solution A, 40g meso-macroporous TiO2 was added, stirred for 1h, pH was adjusted to 5.0 with ammonia water, stirred for 30min, rotary evaporated at 70℃ for 4h, dried at 120℃ overnight, and calcined at 450℃ for 3h to obtain a 20wt% Mo-containing solution. 12 Bi 1.5 Fe 1.5 5C 0.2 G 0.2 K 0.5 O and 80wt% TiO2 catalyst.12 Bi 1.5 Fe 1.5 5C 0.2 G 0. 2K 0.5 O / TiO2 powder was tabletted, formed at 10 MPa, and sieved into 20-40 mesh particles for reaction evaluation.
[0059] Figure 1 , 2 This is a field emission scanning electron microscope (FESEM) image of the mesoporous-macroporous TiO2 in Example 1. Figure 1 , 2 As shown, the TiO2 prepared in Example 1 has a multi-level pore structure of ordered mesopores and macropores.
[0060] Example 2
[0061] Dissolve 6.5g P123 in 75mL ethanol, stir at room temperature for 30min, add 7g hydrochloric acid and stir for 5min, add 5.5g acetic acid and stir for 5min, continue to stir at 60℃ for 2h. Add 15g PMMA balls and stir at room temperature for 6h, add 8.5g titanium isopropoxide and stir at room temperature for 3h. Aging at 35℃ for 5 days. Calcinate at 350℃ in air for 4h to obtain meso-macroporous TiO2. The N2 adsorption and desorption experiment shows that the specific surface area of TiO2 is 223m 2 ·g -1 The average pore size of the macropores is 289nm, and the average pore size of the mesopores is 14nm.
[0062] In a round-bottom flask, 10.59 g (NH4)6MoO 24 ·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 2.60g Ce(NO3)3·6H2O, 0.23g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred at room temperature for 30min to obtain solution B. At 50℃, solution B was added dropwise to solution A, 10g meso-macroporous TiO2 was added, stirred for 1h, pH was adjusted to 6.0 with ammonia water, stirred for 30min, dried at 120℃ overnight, and calcined at 400℃ for 3h. A 50wt% Mo-containing 12 Bi 1. 5Fe 1.5 5C 1.2 G 0.1 K 0.5 O and 50wt% TiO2 catalyst.12 Bi 1.5 Fe 1.5 5C 1.2 G 0.1 K 0.5 O / TiO2 powder was tabletted, formed at 10 MPa, and sieved into 20-40 mesh particles for reaction evaluation.
[0063] Example 3
[0064] Take 6g F127, dissolve it in 75ml ethanol, stir at room temperature for 30min, add 12g hydrochloric acid and stir for 10min, continue to stir at 40℃ for 2h. Add 6g PS balls, stir at room temperature for 6h, add 1.7g titanium isopropoxide, stir at room temperature for 3h. Aging at 40℃ for 5 days. Calcinate at 600℃ in air for 4h to obtain meso-macroporous TiO2. The N2 adsorption and desorption experiment shows that the specific surface area of the catalyst is 197m 2 ·g -1 The average pore size of the macropores is 278nm, and the average pore size of the mesopores is 15nm.
[0065] In a round-bottom flask, 10.59 g (NH4)6MoO 24 ·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 2.60g Ce(NO3)3·6H2O, 0.68g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred at room temperature for 30min to obtain solution B. At 50℃, solution B was added dropwise to solution A, 4.2g meso-macroporous TiO2 was added, and after stirring for 1h, urea was used to adjust pH=7.0, and after stirring for 30min, it was rotary evaporated at 80℃ for 3h, dried at 120℃ overnight, and calcined at 450℃ for 3h. A molten-liquid containing 70wt% Mo was obtained. 12 Bi 1.5 Fe 1.5 5C 1.2 G 0.3 K 0.5 O and 30wt% TiO2 catalyst. 12 Bi 1.5 Fe 1.5 5C 1.2 G 0. 3K 0.5 O / TiO2 powder was tabletted, formed at 10 MPa, and sieved into 20-40 mesh particles for reaction evaluation.
[0066] Example 4
[0067] Dissolve 6g F127 in 75mL ethanol, stir at room temperature for 30min, add 6g hydrochloric acid and stir for 5min, add 6g acetic acid and stir for 5min, continue to stir at 40℃ for 2h. Add 15g PS balls and stir at room temperature for 6h, add 8.5g titanium isopropoxide and stir at room temperature for 3h. Aging at 50℃ for 5 days. Calcinate at 450℃ in air for 4h to obtain meso-macroporous TiO2. The N2 adsorption and desorption experiment shows that the specific surface area of the catalyst is 268m 2 ·g -1 The average pore size of the macropores is 303nm, and the average pore size of the mesopores is 16nm.
[0068] In a round-bottom flask, 10.59 g (NH4)6MoO 24 ·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 0.87g Ce(NO3)3·6H2O, 0.45g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred for 30min at room temperature to obtain solution B. At 50℃, solution B was added dropwise to solution A, 20g meso-macroporous TiO2 was added, stirred for 1h, pH was adjusted to 5.0 with sodium hydroxide, stirred for 30min, rotary evaporated at 70℃ for 4h, dried at 120℃ overnight, and calcined at 450℃ for 3h to obtain a 33wt% Mo-containing solution. 12 Bi 1.5 Fe 1.5 5C 0.4 G 0.2 K 0.5 O and 67wt% TiO2 catalyst. 12 Bi 1.5 Fe 1.5 5C 0. 4G 0.2 K 0.5 O / TiO2 powder was tabletted, formed at 10 MPa, and sieved into 20-40 mesh particles for reaction evaluation.
[0069] Example 5
[0070] Dissolve 6g F127 in 75mL ethanol, stir at room temperature for 30min, add 6g hydrochloric acid and stir for 5min, add 6g acetic acid and stir for 5min, continue to stir at 40℃ for 2h. Add 15g PS balls and stir at room temperature for 6h, add 8.5g titanium isopropoxide and stir at room temperature for 3h. Aging at 30℃ for 5 days. Calcinate at 450℃ in air for 4h to obtain meso-macroporous TiO2. The N2 adsorption and desorption experiment shows that the specific surface area of the catalyst is 268m 2 ·g -1 The average pore size of the macropores is 303nm, and the average pore size of the mesopores is 16nm.
[0071] In a round-bottom flask, 10.59 g (NH4)6MoO 24 ·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 1.74g Ce(NO3)3·6H2O, 0.23g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred for 30min at room temperature to obtain solution B. At 50℃, solution B was added dropwise to solution A, 15g meso-macroporous TiO2 was added, stirred for 1h, pH was adjusted to 5.5 with ammonia water, stirred for 30min, rotary evaporated at 70℃ for 4h, dried at 120℃ overnight, and calcined at 500℃ for 3h to obtain a 40wt% Mo-containing solution. 12 Bi 1.5 Fe 1.5 5C 0.8 G 0.1 K 0.5 O and 60wt% TiO2 catalyst. 12 Bi 1.5 Fe 1.5 5C 0.8 G 0. 1K 0.5 O / TiO2 powder was tabletted, formed at 10 MPa, and sieved into 20-40 mesh particles for reaction evaluation.
[0072] Comparative Example 1
[0073] The catalyst Mo was prepared by the same preparation process as in Example 1 without adding Ce(NO3)3·6H2O. 12 Bi 1.5 Fe 1.5 5gDJ 0.2 K 0.5 O / TiO2.
[0074] Comparative Example 2
[0075] The catalyst Mo was prepared by the same preparation process as in Example 2 without adding Gd(NO3)3·6H2O. 12 Bi 1.5 Fe 1.5 5C 0.2 K 0.5 O / TiO2.
[0076] Comparative Example 3
[0077] The same preparation process as in Comparative Example 1 was used to prepare the catalyst Mo without adding Ce(NO3)3·6H2O and adding 0.90 g Gd(NO3)3·6H2O. 12 Bi 1.5 Fe 1.5 5gDJ 0.4 K 0.5 O / TiO2.
[0078] Comparative Example 4
[0079] The same preparation process as in Comparative Example 2 was used to prepare the catalyst Mo without adding Gd(NO3)3·6H2O and adding 2.82 g Ce(NO3)3·6H2O. 12 Bi 1.5 Fe 1.5 5C 1.3 K 0.5 O / TiO2.
[0080] Comparative Example 5
[0081] The catalyst Mo was prepared by the same preparation process as in Example 3 without adding Ce(NO3)3·6H2O and Gd(NO3)3·6H2O. 12 Bi 1.5 Fe 1.5 5K 0.5 O / TiO2.
[0082] Comparative Example 6
[0083] In a round-bottom flask, 10.59 g (NH4)6MoO 24·4H2O was dissolved in 80mL water at 50℃ and stirred for 30min to obtain solution A. 3.64g Bi(NO3)3·5H2O, 3.03g Fe(NO3)3·9H2O, 7.28g Co(NO3)2·6H2O, 0.43g Ce(NO3)3·6H2O, 0.45g Gd(NO3)3·6H2O and 0.25g KNO3 were dissolved in 20mL 5M HNO3+20mL H2O solution and stirred for 30min at room temperature to obtain solution B. At 50℃, solution B was added dropwise to solution A, stirred for 1h, pH was adjusted to 5.5 with ammonia water, stirred for 30min, dried at 120℃ overnight, and calcined at 450℃ for 3h to obtain Mo. 12 Bi 1.5 Fe 1.5 5C 0.2 G 0.2 K 0.5 The powder was tabletted, formed at 10 MPa, and sieved into particles of 20-40 mesh for reaction evaluation.
[0084] Comparative Example 7
[0085] The same preparation process as in Example 1 was adopted for preparation, and commercial TiO2 was added to carry out a precipitation deposition process to obtain the catalyst.
[0086] The catalysts obtained in the above Examples 1 to 5 and Comparative Examples 1 to 7 are applied to the selective oxidation of isobutylene to prepare MAL. The specific evaluation process is as follows:
[0087] 3.0g of quartz sand was spread on the lower layer of the reaction tube, 1mL of the tableted catalyst was mixed with 1mL of quartz sand to fill the catalyst, and 3.0g of quartz sand was spread on the upper layer of the catalyst. The reaction conditions were: temperature of 360-420℃, atmospheric pressure, and the volume space velocity of the raw gas isobutylene relative to the catalyst was 9200h-1. -1 , the air velocity ratio of air to isobutylene was 96:4. When the reactor temperature, gas flow rate, etc. were stable (1h), samples were taken for analysis to determine the isobutylene conversion rate and MAL yield. The results are shown in Table 1 below.
[0088] Table 1
[0089]
[0090] As shown in Table 1, when the catalysts obtained in Examples 1-5 and Comparative Examples 1-7 are used to catalyze the selective oxidation of isobutylene to prepare methacrolein, the conversion rates are basically the same, but the catalyst in Example 1-5 has a higher selectivity for the target product.
[0091] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A multi-level porous molybdenum-bismuth composite metal oxide catalyst, characterized in that: The general formula of the multi-level porous molybdenum-bismuth composite metal oxide catalyst is Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O / TiO2, wherein 0<x≤1.2, 0<y≤0.3; the multi-level porous molybdenum-bismuth composite metal oxide catalyst comprises a carrier and a composite metal oxide, the composite metal oxide is dispersed in the carrier, the carrier is multi-level porous TiO2, and the composite metal oxide is Mo 12 Bi 1.5 Fe 1.5 5C x G y K 0.5 O.
2. The multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 1, characterized in that: The weight percentage of the carrier to the catalyst is 30% to 80%.
3. A method for preparing a multi-level porous molybdenum-bismuth composite metal oxide catalyst, which is a deposition precipitation method, characterized in that: The steps include: Step 1, preparing a multi-level porous TiO2 carrier; Step 2, preparing a solution containing a Mo precursor, a Bi precursor, a Fe precursor, a Co precursor, a Ce precursor, a Gd precursor, and a K precursor; Step 3, mixing the multi-level porous TiO2 carrier with the solution described in step 2, adding a precipitant for deposition and precipitation, and obtaining a multi-level porous molybdenum-bismuth composite metal oxide catalyst.
4. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 3, characterized in that: The preparation method of the multi-level porous TiO2 carrier comprises the following steps: uniformly mixing a mesoporous template agent and a macroporous template agent, adding a titanium precursor, aging, drying and calcining to obtain the multi-level porous TiO2 carrier.
5. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 4, characterized in that: The mesoporous template agent is F127 and / or P123; the macroporous template agent is PS ball and / or PMMA ball.
6. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 3, characterized in that: The Mo precursor is ammonium molybdate and / or molybdenum trioxide, and the Bi precursor, Fe precursor, Co precursor, Ce precursor, Gd precursor, and K precursor are nitrates or chlorides of Bi, Fe, Co, Ce, Gd, and K.
7. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 3, characterized in that: The precipitant is at least one of ammonia water, urea and sodium hydroxide, and the amount of the precipitant added is such that the pH value of the mixed solution is 5.0-7.
0.
8. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 3, characterized in that: The preparation method of the multi-level porous TiO2 carrier comprises the following steps: The mesoporous template is dissolved in ethanol, hydrochloric acid and / or acetic acid are added, and stirred; the macroporous template is added, stirred, and then the titanium precursor is added, aged, dried, and calcined to obtain a multi-level porous TiO2 carrier.
9. The method for preparing the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 3, characterized in that: The drying method is rotary evaporation and / or oven drying.
10. Use of the multi-level porous molybdenum-bismuth composite metal oxide catalyst according to claim 1 or 2 in the selective oxidation of isobutylene to prepare methacrolein.
Citation Information
Patent Citations
Method for producing unsaturated aldehyde and / or unsaturated carboxylic acid
CN102627537A
Catalyst and method for directly preparing light olefins from synthesis gas by one-step process
CN106311317A
Composite metal oxide catalyst and preparation method thereof
CN108421549A
Catalyst as well as preparation method and application thereof
CN109833881A
Catalyst for preparing methylacrolein through isobutene oxidation and preparation and application of catalyst
CN112871193A
Cited By
Catalyst and method for producing unsaturated aldehyde compound or unsaturated carboxylic acid compound
WO2026211280A1